The Association Study Between Cytokines and the Risk for Cerebral Palsy - Baotian Wang; Fan Wang; Li Yang; Junhong Jiang; Jiulai Tang; De Wu (Mediators of Inflammation)
Conclusions: This study revealed significant associations between NSE and TNF-α and CP risk, suggesting that NSE and TNF-α might be useful blood biomarkers for identifying patients at high risk of CP.